2020
DOI: 10.1002/joa3.12432
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of weight loss in obese atrial fibrillation patients attending a specialist arrhythmia clinic and its impact on ablation outcomes

Abstract: Background The feasibility of significant weight reduction in a specialist arrhythmia service, and its impact on atrial fibrillation (AF) ablation outcomes are unclear. We aimed to assess these factors in a real‐world cohort in the United Kingdom. Methods Patients from one specialized arrhythmia clinic were instructed to follow the “Intermittent Fasting 5:2 diet” (“diet group”, n = 50), and their outcomes were compared to a propensity matched cohort who received no specific dietary advice (“control group”, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…On the contrary, several studies have pointed out the obesity paradox effect owing to the favorable cardiovascular outcomes observed on anticoagulated AF patients with obesity compared to nonobese 4 . Furthermore, one study suggested weight loss in obese patients who underwent AF ablation, surprisingly, did not improve AF recurrence rates 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, several studies have pointed out the obesity paradox effect owing to the favorable cardiovascular outcomes observed on anticoagulated AF patients with obesity compared to nonobese 4 . Furthermore, one study suggested weight loss in obese patients who underwent AF ablation, surprisingly, did not improve AF recurrence rates 5 …”
Section: Introductionmentioning
confidence: 99%
“… 4 Furthermore, one study suggested weight loss in obese patients who underwent AF ablation, surprisingly, did not improve AF recurrence rates. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 and Additional file 1: Table S4 summarizes the characteristics of the included studies. One randomized open-labeled,clinical trial [21] with 133 (weight loss = 67, control = 66) patients and seven cohorts with 1150 patients (prospective [22][23][24][25][26][27] = 6, retrospective [19] = 1) were included. Overall, these studies were published between 2014 and 2021.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…65 Despite these described positive responses to risk factor management programmes in AF, other studies could not confirm these beneficial effects, suggesting, that there are potentially non-weight responsive forms of AF in some patients. [70][71][72][73] Previous work showed that idiopathic AF patients develop cardiovascular disease more often, at a younger age and with a more severe disease profile compared to healthy sinus rhythm controls, suggesting the presence of subclinical comorbidities. 74 Similarly, in a recent retrospective study young AF patients (mean age 46 years), only 11% of patients were free of AF risk factors or comorbidities, whereas 44% had hypertension and 25% had a family history of AF.…”
Section: Af Risk Factorsmentioning
confidence: 99%